Digital Football Fandom as Participatory Culture: Study from @utdfocusid on Platform X - Andhika Widy Nugroho; Aulia Rahmawati (Lavish Opulent Education, 2026)
This study examines the forms of participatory culture within the Manchester United fandom on social media platform X through the account @utdfocusid. Employing a qualitative approach with Christine Hine's virtual ethnography method, data were collected through virtual observation of three strategically selected match periods involving Manchester United against Grimsby Town, Liverpool, and Arsenal, alongside supplementary content outside these periods. Data analysis followed the interactive model by Miles, Huberman, and Saldana. The findings demonstrate that @utdfocusid embodies all four dimensions of Participatory Culture, Affiliations manifested through memes and hashtags as collective identity markers; Expressions embodied in sarcastic humor and emoticon use as emotional communication; Circulations occurring through live tweets and multi-directional fan interactions; and Collaborative Problem Solving evident in real-time tactical discussions and historical rivalry threads that collectively produce richer community knowledge. These findings establish that digital fandom operates as a complex communication ecosystem where collective identity, solidarity, and shared knowledge are actively constructed, extending well beyond mere emotional expression